The Effect of Multiple Choice Test Number of Alternatives on The Estimation of a person’s Ability and the Psychometric Properties of a Test and its Items According to Rasch Model in Item Response Theory (IRT) - al-Shraifin, Nedal; Ta’mnah, Eman (Jordan Journal of Educational Sciences, 2009)
This study investigated the effect of multiple choice test number of alternatives on the estimations of: a Person’s ability, item difficulty, and the information function of test and its items. To achieve the study objectives, a multiple choice achievement test consisting of 40 items in tenth grade maths was constructed. The test took three different forms in terms of the number of alternatives: Form One with three alternatives, Form Two with four alternatives, and Form Three with five alternatives. The test forms were applied on a total sample of 600 male and female students, with 200 students assigned to each form. Data obtained for each form of the test were analyzed separately using (BIGSTEPS) and (BILOG-MG). The study findings revealed the following: there were no statistically significant differences (α=0.05) among the standard error means of item in the estimation of difficulty parameters, and no statistically significant differences (α=0.05) among a person’s reliability coefficients due to number of alternatives.However, item reliability coefficients were equal and there were statistically significant differences (α=0.05) among the standard error means of a person’s ability parameters, and such estimations in a person’s ability were more accurate in Form One of the test than in Form Three, and in Form Two of the test than in Form Three whereas such estimations were similar in Forms One and Two. In addition to that, Form One of the test yielded more information at the low ability level but at the medium and high ability levels, the most information was in Form Three of the test, and there were statistically significant differences (α=0.05) among criterion validity coefficients in favor of Form Two of the test